2011
DOI: 10.1007/s10620-011-2013-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nucleoside (Tide) Analogues in Patients with Hepatitis B-Related Acute Liver Failure

Abstract: Background & Aims The efficacy of nucleoside(tide) analogues (NA) in the treatment of acute liver failure due to hepatitis B virus (HBV-ALF) remains controversial. We determined retrospectively the impact of NAs in a large cohort of patients with HBV-ALF. Methods The US Acute Liver Failure Study Group, a 23-site registry prospectively enrolled 1,413 patients with ALF with different etiologies between 1998 and 2008. Of those, 105 patients were identified as HBV-ALF patients, of whom we excluded those without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 24 publications
0
26
0
3
Order By: Relevance
“…This explains why some patients present with borderline or nondetectable HBV DNA, a situation that may be anticipated more often when a prolonged delay exists between the onset of symptoms and first assessment. 12,14 It can be argued that complete clinical recovery in these instances may depend more on the adequacy of hepatocellular regeneration rather than the rate or degree to which viral replication is suppressed by antiviral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This explains why some patients present with borderline or nondetectable HBV DNA, a situation that may be anticipated more often when a prolonged delay exists between the onset of symptoms and first assessment. 12,14 It can be argued that complete clinical recovery in these instances may depend more on the adequacy of hepatocellular regeneration rather than the rate or degree to which viral replication is suppressed by antiviral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…48 A large retrospective review, however, found no difference in spontaneous and overall survival in patients with ALF from hepatitis B infection who were and were not treated with a nucleoside(-tide) analogue. 49 The role of corticosteroids in AIH ALF is unclear. Immunosuppression, usually steroids followed by azathioprine, is recommended for chronic AIH; however, the use in ALF is controversial.…”
Section: Medicationsmentioning
confidence: 99%
“…Most of these studies recruited patients before they had progressed to more advanced hepatic encephalopathy (HE stages 3 or 4). In a study recruiting patients with more advanced liver failure, no benefit of nucleoside on survival was observed [37], but those authors still concluded that nucleos(t)ide analogues would be indicated in such patients to reduce viral load prior to potential liver transplantation. It is likely that early intervention is crucial.…”
Section: Treatment To Ameliorate Course Of Acute Hepatitis Bmentioning
confidence: 99%